EFEKTIVITAS BIOFUNGISIDA Trichoderma koningii TERHADAP PENCEGAHAN PENYAKIT JAMUR AKAR PUTIH DI PEMBIBITAN BATANG BAWAH TANAMAN KARET (Hevea brasiliensis) - Gema Tarigan; Mardiana Wahyuni; Guntoro . (Institut Teknologi Sawit Indonesia, 2019)
One of the main obstacles in rubber cultivation is the white root fungus (JAP) attack which caused by Rigidophorus ligonosus. This pathogen infects rubber plants from the nursery until the mature plants. Efforts to control the disease have been carried out by chemical, technical culture and use of biological agencies. This research was conducted at the STIP-AP Medan in January 2017 to June 2017, this study used a non-factorial Randomized Block Design (RBD) with four replications and four treatments. Using Trichoderma koningii with somes doses were 20 grams, 30 grams, and 40 grams/seedling. The results of this study indicate that the biofungicide application of Trichoderma koningii 30 g/seedling produces the greatest inhibition of the rubber plants seedling nursery against the growth of pathogens Rigidoporus lignosus.